Fritz Leiber Remembered, 1910-1992: Grand Master of Science Fiction and Fantasy - Leiber, Fritz; Priest, Prudence; Kassel, Vampyre Mike; Harder, Greg; et. al. (San Francisco, CA: Familiar Productions, 1992)
Fritz Leiber Remembered, 1910-1992: Grand Master of Science Fiction and Fantasy. Video documentary, 1992. Produced by Familiar Productions, San Francisco (Calif.). DVD Rip (originally on VHS), 352 x 240 MPEG-1/2 29.97 FPS. Converted to H.264 MP4. Available on YouTube at https://youtu.be/uc-z-s5Ymn4 Fritz Leiber's brilliant 50 year career as a writer of science fiction and fantasy was marked by over 30 awards. He earned seven Hugos, four Nebulas, and numerous Grand Master of Life Achievement awards. His novels and stories influenced and impressed many other writers while captivating readers for decades. This hour long video is an informal tribute to a talented writer, good friend, and perfect gentleman - Fritz Leiber, Jr. The program includes intimate interviews with Fritz, his fellow writers, friends, and family. Video footage includes book signings, panels, and participation in a Heathen Sumbel. Featured are statements by Fritz Leiber, Justin Leiber, Margo Skinner Leiber, Harlan Ellison, Judith Merrill, Poul Anderson, Greg Bear, Susan Dexter, Megan Lindholm, S.P. Somtow, and others. This hour long video is our informal tribute to a talented writer, good friend, and perfect gentleman - Fritz Leiber, Jr. The program includes intimate interviews with Fritz, his fellow writers, friends, and family. We feature statements by Fritz Leiber, Justin Leiber, Margo Skinner Leiber, Harlan Ellison, Judith Merril, Poul Anderson, Greg Bear, Susan Dexter, Megan Lindholm, S.P. Somtow, and others. Produced by Greg Harder; Computer Graphics by Owen Rowley; Music by Robyn North Star; Cover Design by Prudence Priest; This digital asset has been authorized by Prudence Priest to the Valdosta State University, Archives and Special Collections to be part of the Prudence Priest Collection of the New Age Movements, Occultism, and Spiritualism Research Library.
1 Electronic records. 1 DVD Disc. Copied to ISO, MPG, MP4. 3.94 GB, 4227296627 bytes. 00:54:37. 1 scan of DVD cover tif, pdf; thumbnail of cover. 1 branding sheet. 34.6 GB (37,163,689,146 bytes).
Keywords: Authors, American Neopagans; Biographies; Documentary films; California; Interviews; Leiber, Fritz, 1910-1992; Nonfiction films